EPCO-09. LONGITUDINAL ANALYSIS OF DIFFUSE GLIOMA REVEALS CELL STATE DYNAMICS AT RECURRENCE ASSOCIATED WITH CHANGES IN GENETICS AND THE MICROENVIRONMENT. (12th November 2021) - Varn, Frederick; Johnson, Kevin; Wade, Taylor; Malta, Tathiane; Sabedot, Thais; Barthel, Floris; Kim, Hoon; Ahmed, Nazia; Datta, Indrani; Barnholtz-Sloan, Jill; Bakas, Spyridon; D'Angelo, Fulvio; et al.
Abstract: Diffuse glioma is characterized by a poor prognosis and a universal resistance to therapy, though the evolutionary processes behind this resistance remain unclear. The Glioma Longitudinal Analysis (GLASS) Consortium has previously demonstrated that therapy-induced selective pressures shape the genetic evolution of glioma in a stochastic manner. However, single-cell studies have revealed that malignant glioma cells are highly plastic and transition their cell state in response to diverse challenges, including changes in the microenvironment and the administration of standard-of-care therapy. To interrogate the factors driving therapy resistance in diffuse glioma, we collected and analyzed RNA- and/or DNA-sequencing data from temporally separated tumor pairs of over 300 adult patients with IDH-wild-type or IDH-mutant glioma. In a subset of these tumor pairs, we complemented these data with single-nucleus RNAseq and multiplex imaging mass cytometry at each time point. Recurrent tumors exhibited diverse changes that were attributable to changes in histological features, somatic alterations, and microenvironment interactions. IDH-wild-type tumors overall were more invasive at recurrence and exhibited increased expression of neuronal signaling programs that reflected a possible role for neuronal interactions in promoting glioma progression. In contrast, recurrent IDH-mutant tumors exhibited a significant increase in proliferative expression programs that correlated with discrete genetic changes. Hypermutation and acquired CDKN2A homozygous deletions associated with an increase in proliferating stem-like malignant cells at recurrence in both glioma subtypes, reflecting active tumor expansion. A transition to the mesenchymal phenotype was associated with the presence of a specific myeloid cell state defined by unique ligand-receptor interactions with malignant cells, providing opportunities to target this transition through therapy. Collectively, our results uncover recurrence-associated changes in genetics and the microenvironment that can be targeted to shape disease progression following initial diagnosis.